الذكاءالروحي وعلاقته بتقديرالذات لدى عينة من تلاميذ الثالثة ثانوي - مولاي.كريمة; لخشاخش,سعدية (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة الحالية إلى معرفة العلاقة بين الذكاء الروحي وتقدير الذات لدى تلاميذ السنة الثالثة ثانوي، والكشف عن الفروق بين تقدير الذات والذكاء الروحي لدى أفراد العينة وفقا لمتغيري الجنس والشعبة. اعتمدت الدراسة على المنهج الوصفي الارتباطي، واستخدم في جمع البيانات والمعطيات الضرورية لهذه الدراسة أداتين وهما: استبيان الذكاء الروحي، واستبيان تقدير الذات وقد بلغ حجم عينة الدراسة (64) تلميذ منهم 45 إناث. حيث تمت المعالجة الإحصائية للبيانات بواسطة الحزمة الإحصائية (SPSS)، الذي سمح بتطبيق الأدوات الإحصائية التالية: معامل الارتباط (T-TEST) لعينة واحدة، معامل الارتباط بيرسون، (T-TEST) لعينتين مستقلتين، إختبار ANOVA. وخلصت نتائج الدراسة إلى: 1-وجود علاقة إرتباطية ذات دلالة إحصائية بين الذكاء الروحي وتقدير الذات لدى تلاميذ الثالثة ثانوي. 2-لا توجد فروق ذات دلالة إحصائية في الذكاء الروحي لدى تلاميذ الثالثة ثانوي تبعا لمتغير الجنس. 3-لا توجد فروق ذات دلالة إحصائية في تقدير الذات لدى تلاميذ الثالثة ثانوي تبعا لمتغير الجنس. 4-لا توجد فروق ذات دلالة إحصائية في الذكاء الروحي لدى تلاميذ الثالثة ثانوي بإختلاف الشعبة. 5-لا توجد فروق ذات دلالة إحصائية في تقدير الذات لدى تلاميذ الثالثة ثانوي بإختلاف الشعبة. The current study aimed to find out the relationship between spiritual intelligence and self-esteem among third-year secondary school students, and to reveal the differences between self-esteem and spiritual intelligence among sample members according to the variables of gender and class. The study relied on the descriptive, correlational approach, and two tools were used to collect the necessary data and data for this study: the Spiritual Intelligence Questionnaire and the Self-Esteem Questionnaire. The study sample size was (64) students, including 45 females. The statistical processing of the data was done using the statistical package (SPSS), which allowed the application of the following statistical tools: the correlation coefficient (T-TEST) for one sample, the Pearson correlation coefficient (T-TEST) for two independent samples, and the ANOVA test. The results of the study concluded: 1- There is a statistically significant correlation between spiritual intelligence and self-esteem among third secondary school students. 2- There are no statistically significant differences in the spiritual intelligence of third secondary school students according to the gender variable. 3- There are no statistically significant differences in the self-esteem of third-year secondary school students according to the gender variable. 4-There are no statistically significant differences in the spiritual intelligence of third secondary school students depending on the section. 5-There are no statistically significant differences in the self-esteem of third secondary school students depending on the class.
Keywords: الذكاء الروحي; spiritual intelligence; تقدير الذات; self-esteem